Keterampilan Proses Sains Mahasiswa dalam Penggunaan Laboratorium Virtual Berbasis Tinkercad pada Materi Gerbang Logika - Wilfrida Mayasti Obina; Adnan Sahar; Evani Doana Nababan; Andi Nurfahrunnisa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze students' science process skills in using Tinkercad-based virtual laboratories on logic gates. The study used a qualitative method with a descriptive case study approach, with subjects being students of the Physics Education Study Program at Musamus University who took the Digital Electronics course in the 2025/2026 academic year. Data collection was carried out systematically through direct observation, questionnaires, and in-depth interviews to obtain an overview of students' science process skills. Indicators used include the skills of observing, predicting, conducting experiments, analyzing and solving problems, and drawing conclusions. The results showed that students' science process skills in using Tinkercad-based virtual laboratories were in the good category, with an average observation score of 73.00% and supported by questionnaire results of 75.83%. The skill of conducting experiments was in the very good category with a percentage of 82.50%. Meanwhile, the skills of analyzing and solving problems and drawing conclusions each reached 75.00%, observation skills were 72.50%, and prediction skills were in the fairly good category with a percentage of 60.00%. These findings indicate that the use of a Tinkercad-based virtual laboratory is effective in supporting the development of students' science process skills through experimental simulation experiences on logic gate material.